2020
DOI: 10.3390/nu12103119
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Changes in Health Behaviours and Body Weight during the COVID-19 Quarantine in Lithuania: The Lithuanian COVIDiet Study

Abstract: The COVID-19 quarantine has caused significant changes in everyday life. This study aimed to evaluate the effect of the quarantine on dietary, physical activity and alcohol consumption habits of Lithuanians and the association between health behaviours and weight changes. An online cross-sectional survey was carried out among individuals older than 18 years in April 2020. The self-administered questionnaire included health behaviour and weight change data. Altogether 2447 subjects participated in the survey. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
265
14
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(332 citation statements)
references
References 23 publications
40
265
14
13
Order By: Relevance
“…The impact of lockdown on food intake among our students was equivocal. Meal patterns remained stable, unlike in previous studies, which showed an increased number of main meals and snacking [5,43], explained by spending more time on cooking, trying new recipes and enjoying food without rushing during lockdown [5]. Even though we didn't find differences in breakfast frequency, number of meals per day, snacking frequency or overall Mediterranean diet adherence, some differences have been recorded between the two study periods.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…The impact of lockdown on food intake among our students was equivocal. Meal patterns remained stable, unlike in previous studies, which showed an increased number of main meals and snacking [5,43], explained by spending more time on cooking, trying new recipes and enjoying food without rushing during lockdown [5]. Even though we didn't find differences in breakfast frequency, number of meals per day, snacking frequency or overall Mediterranean diet adherence, some differences have been recorded between the two study periods.…”
Section: Discussioncontrasting
confidence: 91%
“…Inevitably, those and similar measures tremendously impacted economy and functioning of society at large [ 4 ], but they also affected everyday life and health behaviors [ 5 ]. Unavoidably, restrictions on travel and outdoor activities, along with physical distancing, self-isolation and quarantine, disarranged routine daily activities, affecting in particular physical activity and eating habits of all age groups [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another online-survey from Lithuania with 2447 participants it was observed that 49.4% ate more than before and 45.1% increased snacking, while intake of fast food, sugary drinks and commercial pastries decreased. A third of respondents described a gain of weight, more often those with overweight and those that were older [ 18 ]. Summarizing the current literature on the effects of confinement and quarantine on nutritional intake and nutritional status during the COVID-19 pandemic it has to be acknowledged that most studies relied on convenience samples that were recruited online.…”
mentioning
confidence: 99%